2019
DOI: 10.1038/s41598-019-48675-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation of spatiotemporal parameters in school children carrying different backpack loads: a cross sectional study

Abstract: The purpose of this study was to analyze spatiotemporal parameters of gait in children using varyingly loaded Backpacks(BP). This cross-sectional study examined 231 schoolchildren (118 boys, 113 girls) aged six to 12 years, carrying a traditional BP to manipulate loading (Crossing Backpack Children Arpenaz 7 Litres, Junior Red Quechua). Load was added to the BPs in increments of 5%, 10%, 15% and 20% of the child’s body weight. Spatio-temporal parameters were measured with the OptoGait system. Significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
(47 reference statements)
1
14
0
1
Order By: Relevance
“…Auch die Verlängerung der Doppelunterstützungsphase, bei der beide Füße gleichzeitig am Boden verbleiben, ist ein Indiz für die Zunahme der Instabilität. Eine reduzierte Ganggeschwindigkeit mit verkürzter Schrittlänge und verlängerter Doppelunterstützungsphase konnten auch in anderen Studien sowohl bei Kindern als auch Erwachsenen gezeigt werden [ 1 , 6 , 27 , 33 ].…”
Section: Diskussionunclassified
“…Auch die Verlängerung der Doppelunterstützungsphase, bei der beide Füße gleichzeitig am Boden verbleiben, ist ein Indiz für die Zunahme der Instabilität. Eine reduzierte Ganggeschwindigkeit mit verkürzter Schrittlänge und verlängerter Doppelunterstützungsphase konnten auch in anderen Studien sowohl bei Kindern als auch Erwachsenen gezeigt werden [ 1 , 6 , 27 , 33 ].…”
Section: Diskussionunclassified
“…This is the first study to present the spatiotemporal gait parameters under four different loading conditions (0%, 10%, 15% and 20% BW) of additional load carried in the backpack by seven-year-old girls and boys. In contrast to other similar research [ 47 , 48 ], the novelty of our study is that only first-grade students who had just started using BPs, were examined. Therefore, the early effects of using BPs were captured.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the scholars reduced their balance phase of walking gait. It demonstrates a higher necessity to use the support limbs for carrying the backpack, favoring the postural stability during the walking gait1 11,22 . Significant adaptations in time-space parameters of walking gait in the 15% and 20% load conditions were also reported in the recent studies of Rashid et al 21 and Paez-Moguer et al 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In the timespace variables such as single support time, double support time, velocity, and stride time, no significant differences were found among the load conditions. Paez-Moguer et al 11 described a linear increase in the double support time according to the increase in the backpack load (5%, 10%, 15%, and 20%). The authors indicated that the most evident differences in the space-time parameters of walking gait occurred between the 15% and 20% loads.…”
Section: Introductionmentioning
confidence: 99%